2001
DOI: 10.1603/0022-0493-94.2.552
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Consequences of Malathion-Specific Resistance in Red Flour Beetle (Coleoptera: Tenebrionidae) and Selection for Resistance in the Absence of Malathion

Abstract: Malathion resistance in the red flour beetle, Tribolium castaneum (Herbst), is a worldwide problem and is very stable once it becomes widespread in natural populations. In the absence of insecticide the proportion of resistant phenotypes may rapidly decline but the development of resistance does not always involve reduced fitness. Malathion-specific resistance in T. castaneum seems not to involve any loss of fitness in laboratory or field conditions. Susceptible beetles were in competition with resistant beetl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 28 publications
(30 reference statements)
0
56
0
5
Order By: Relevance
“…However, despite the extensive literature on the subject, there are relatively few empirical studies that confirm that investment in such adaptations exacts a cost (Minkoff and Wilson, 1992;Carriere et al, 1994Carriere et al, , 1995Yamamoto et al, 1995;Chevillon et al, 1997;Alyokhin and Ferro, 1999;Boivin et al, 2001). Some authors have failed to reveal any detrimental effects of insecticide resistance (Follett et al, 1993;Tang et al, 1997Tang et al, , 1999Baker et al, 1998) and some have shown such organisms to be even more successful than their susceptible counterparts in the absence of insecticides (Omer et al, 1992;Bloch and Wool, 1994;White and Bell, 1995;Mason, 1998;Haubruge and Arnaud, 2001). In other studies, some measures of fitness have been negatively affected, others positively (Brewer and Trumble, 1991) and different strains of insect, exhibiting resistance to the same compound, can show opposite associations (Chevillon et al, 1997;Hollingsworth et al, 1997;Oppert et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the extensive literature on the subject, there are relatively few empirical studies that confirm that investment in such adaptations exacts a cost (Minkoff and Wilson, 1992;Carriere et al, 1994Carriere et al, , 1995Yamamoto et al, 1995;Chevillon et al, 1997;Alyokhin and Ferro, 1999;Boivin et al, 2001). Some authors have failed to reveal any detrimental effects of insecticide resistance (Follett et al, 1993;Tang et al, 1997Tang et al, , 1999Baker et al, 1998) and some have shown such organisms to be even more successful than their susceptible counterparts in the absence of insecticides (Omer et al, 1992;Bloch and Wool, 1994;White and Bell, 1995;Mason, 1998;Haubruge and Arnaud, 2001). In other studies, some measures of fitness have been negatively affected, others positively (Brewer and Trumble, 1991) and different strains of insect, exhibiting resistance to the same compound, can show opposite associations (Chevillon et al, 1997;Hollingsworth et al, 1997;Oppert et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is likely that the genetic background of the insects does not influence their fitness (Haubruge and Arnaud, 2001). Both of these observations may explain the widespread occurrence of malathion-specific resistance in this species.…”
Section: Introductionmentioning
confidence: 94%
“…In T. castaneum, no trade-off has been reported between malathion-specific resistance and the fitness of the insects (Beeman and Nanis, 1986;Haubruge and Arnaud, 2001). In addition, it is likely that the genetic background of the insects does not influence their fitness (Haubruge and Arnaud, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through such monitoring, it is possible to evaluate the efficiency of commonly used management strategies to delay resistance development. Studies regarding phosphine resistance management are of particular interest to control resistant populations (Haubruge & Arnaud, 2001).…”
Section: Introductionmentioning
confidence: 99%